Konsep Judicial Pardon (Pemaafan Hakim) dalam Masyarakat Adat di Indonesia - Farikhah, Mufatikhatul - (Jurnal Media Hukum, 2018)
ABSTRACTRenewal of the criminal law puts a new conception of Judicial Pardon in the formulation of Article 56 paragraph (2) of the draft of the Criminal Code concept of 2016. The author is believed the existence of the concept in indigenous Indonesian society, so that it can find the best concept is characterized by Indonesia. The article is based on the results of normative legal research with the method of conceptual approach and statue Approach. The concept of Judicial Pardon has appeared in various forms of implementation within the Indonesian Community, including in Indigenous Batak Karo, Lampung Menggala, Minangkabau, Java and Aceh. The concept of forgiveness that exists within indigenous peoples requires the forgiveness of the victim, and does not necessarily eliminate the criminal. There are sanctions provided but the sanctions are not only for the interests of the victim and the perpetrator but also to restore the balance that has been damaged by the crime. The sanctions in the form of indemnification or other forms agreed by the parties including the public, through a peaceful resolution mechanism without involving the Court